2013
DOI: 10.1089/met.2012.0115
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome, Adiponectin, and Cardiovascular Risk in Spain (The Segovia Study): Impact of Consensus Societies Criteria

Abstract: Our results show: (1) A higher estimated prevalence of metabolic syndrome according to IDF and CS criteria. (2) Low educational level was independently associated with metabolic syndrome. A high level of physical activity and a daily alcohol intake of less than 15 grams/day were inversely associated with metabolic syndrome. (3) Metabolic syndrome increases the predicted CVD risk. (4) Adiponectin levels are not inversely related to insulin resistance in subjects with high cardiovascular risk and metabolic syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 49 publications
0
13
1
2
Order By: Relevance
“…According to a meta-analysis by Kastorini et al 8 , the MS occurrence in the world according to the IDF definition ranges from about 7.4% to about 50%. In Western countries, the prevalence of the MS according to the IDF definition is lower comparing to the results of our research, ranging from 20% to 30% (for example in Spain, 24.3%) 9 .…”
Section: Discussioncontrasting
confidence: 93%
“…According to a meta-analysis by Kastorini et al 8 , the MS occurrence in the world according to the IDF definition ranges from about 7.4% to about 50%. In Western countries, the prevalence of the MS according to the IDF definition is lower comparing to the results of our research, ranging from 20% to 30% (for example in Spain, 24.3%) 9 .…”
Section: Discussioncontrasting
confidence: 93%
“…This observed prevalence was slightly higher than the prevalence estimated around the world (between 20% and 25%) [4]. In fact, the mean prevalence of MS in Brazil was higher than that reported in such European countries as Portugal (27.6%) [24], Spain (26.6%) [25], France (25% in males and 15.3% in females) [26] and Italy (28% in males and 26% in females) [27]. It was also higher than in the United States of America (22.9%) [7] and some Latin American countries: Mexico (26.6%) [8] and Peru (18.1%) [10].…”
Section: Discussionmentioning
confidence: 75%
“…Other studies conducted in Iran and other parts of the world reported a higher prevalence for MS. The prevalence of this disorder among adults was 38.5% in the United States [9], 27.8% in Spain [32], 21.1% in France [10], 25.9% in Norway [33], 54.8% in Mexico [11], 35.73% in Morocco [2], 30% in Tanzania [34], 25% in Korea [35], 21.3 -39% in China [12,13], 40-50% in India [36], 21% in Saudi Arabia [14], 36.3% in Jordan [37], 33.5% in Turkey [15], and 21.9% -32% in different regions of Iran [16][17][18][19][20][21][22][23]. Possible reasons for this difference and lower prevalence of MS, are racial and regional differences, age differences between studies, and the use of different definitions for MS.…”
Section: Discussionmentioning
confidence: 99%